A review of the genus Chrysosplenium as a traditional Tibetan medicine and its preparations. (23rd May 2022) - Zhao, Jiajia; Qiu, Xiang; Zhao, Yunyan; Wu, Rui; Wei, Panhong; Tao, Chengtian; Wan, Li
Abstract: Ethnopharmacological relevance: Plants of genus Chrysosplenium have a long history of application and are distributed in many countries, especially in Tibetan regions of China. The genus has been used locally in the treatment of various hepatobiliary diseases such as "Chiba disease" (related to cholecystitis, cholelithiasis, acute icteric hepatitis, and acute liver necrosis in modern medicine). Aim of the review: This review summarizes and critically analyzes the aspects of the botanical morphology and distribution, traditional uses, phytochemistry, pharmacological activities, quality control, and development status of preparations of the genus Chrysosplenium . Moreover, the future research direction and focus of the genus are also discussed. We hope to provide a valuable reference for researchers who are interested in the genus Chrysosplenium . Materials and methods: The relevant information of the genus Chrysosplenium was gathered through electronic databases from 1968 to 2021, including PubMed, Web of Science, ScienceDirect, Google Scholar, Springer, CNKI, and Wan Fang, as well as PhD, MSc thesis, Chinese Pharmacopoeia (2020 edition), Tibetan medicine monographs. In addition, plant names were verified by "The Plant List" (The Plant List Database, http://www.theplantlist.org ). Results: Based on existing studies of chemical compositions, more than 90 compounds have been identified from Chrysosplenium species, including flavonoids, triterpenoids, volatile oils, steroids, alkaloids, and other compounds. The highly hydroxylated and methoxylated flavonoids and triterpenoids are the main active components. In addition, many studies have shown that the extracts and some components isolated from the genus Chrysosplenium have a variety of pharmacological activities, such as anti-tumor, antibacterial, anti-viral, hepatoprotective, and insecticidal properties. Furthermore, there are only 9 preparations with Chrysosplenium species as one of the medicinal materials. Among these preparations, C. nudicaule is used more and other Chrysosplenium species are rarely involved. Conclusions: Most medicinal species of Chrysosplenium have not only good therapeutic effects in traditional uses, but also a great potential for development in modern pharmaceutical studies. However, the material basis and mechanism of action of this genus have not been well explained. Therefore, further systematic and comprehensive research on the genus Chrysosplenium is still required to provide a scientific basis for its clinical applications. Graphical abstract: Image 1